Friction and wear behavior of microwave sintered Al2O3/TiC/GPLs ceramic sliding against bearing steel and their cutting performance in dry turning of hardened steel. Issue 17 (1st December 2017) - Wang, Jiaao; Cheng, Yu; Zhang, Yong; Yin, Zengbin; Hu, Xiao; Yuan, Qin
Abstract: An Al2 O3 /TiC/GPLs (ATG) composite ceramic tool material was fabricated by microwave sintering. The tribological properties of ATG during sliding against GCr15 bearing steel were studied, to investigate the effects of sliding speed and normal load on the friction coefficient and wear rate. In addition, the cutting performance of ATG tools for machining of hardened alloy 40Cr steel was experimentally studied and compared with those of commercial tools. The results showed that the added graphene platelets enhanced the wear resistance and reduced the friction coefficient of the tool material. Furthermore, upon adding graphene platelets, the ability of the tools to resist breakage and their cutting depth improved. The cutting length of the microwave- sintered ATG ceramic tools was approximately 125% higher than that of hot-pressed ceramic tools and 174% higher than that of cemented carbide tools.